Subchronic exposure of rats to sublethal dose of microcystin-YR induces DNA damage in multiple organs - Filipič, Metka (Radiology and oncology (Ljubljana), 2007)
Background. Microcystins (MCs) are cyclic heptapeptides that are considered tobe liver specific toxins. They are potent tumour promoters and recent studies indicate that they are also genotoxic. In this study we measured DNA damage in lymphocytes, liver, kidney (cortex and medulla), lung, spleen and brain cells of male Fisher F344 rats that were exposed to sublethal dose (every second day 10 Ugžkg b.w.č i.p) of microeysrin-YR (MCYR) for one month. Methods. At the end of exposure the animals were sacrificed, the lymphocytes were isolated from blood taken from jugular vein, liver cells were obtained byperfusion with collagenase A and the cells from other organs were isolated by incubating small tissue pieces with eollagenase A. The DNA damage in isolated cells was measured with the single cells gel electrophoresis (SCGE) also called the comet assay. Results. A significant increase of the % tail DNAin MCYR-exposed animals compared to the nonexposed control ones was observed in brain (2.5 fold), liver (2.1 fold), kidney medulla (1.9 fold), kidney cortex (1.8 fold) and lung (1.7 fold) cells, while the DNA from lymphocytes and spleen cells was not affected. Conclusion. This study demonstrated that subehronic exposure to sublethal doses of MCs can induce systemicgenotoxicity in mammals, and it affects not only the liver but also other vital organs.
Keywords: biokemija; DNA; mikrocistin; podgane; poskusi